ROLE OF MULTICULTURAL EDUCATION PROGRAMS IN MORAL DEVELOPMENT OF AMERICAN SCHOOLCHILDREN - Svitlana Lukianchuk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The aim of the article is to analyze the role of multicultural education programs in moral development of schoolchildren in the USA. It is noted that one of the top priority tasks of school is the development of such traditional American values as freedom, democracy, racial and national tolerance and others. For this purpose some changes in educational programs are being made. It is highlighted that implementation of courses and programs of multicultural education has become an important part of the educational process. These programs are of interdisciplinary character and they are integrated into educational programs of moral and social disciplines. According to their aims and priorities all courses and programs of multicultural education are divided into three groups: content-oriented, person-oriented, and socially-oriented. The analysis of the results of their implementation makes it possible for the author to conclude that integration of the programs of multicultural education into the educational process makes great contribution to the moral development of American schoolchildren.